Albinism in plants – far beyond the loss of chlorophyll: Structural and physiological aspects of wild‐type and albino royal poinciana (Delonix regia) seedlings. (10th August 2020) - Silva, L. A. S.; Sampaio, V. F.; Barbosa, L. C. S.; Machado, M.; Flores‐Borges, D. N. A.; Sales, J. F.; de Oliveira, D. C.; Mayer, J. L. S.; Kuster, V. C.; Rocha, D. I.
Abstract: The partial or complete loss of chlorophylls, or albinism, is a rare phenomenon in plants. In the present study, we provide the first report of the occurrence in albino Delonix regia seedlings and describe the morpho‐physiological changes associated with albinism. Wild‐type (WT) and albino seedlings were characterized. Leaflets samples were processed following common procedures for analysis with light, scanning and transmission electron microscopy. The chlorophyll a fluorescence parameters and the carbohydrate, lipid and soluble protein content were also determined in leaf and cotyledon samples of both albino and WT seedlings. Albino seedlings showed reduced growth. They also had lower chlorophyll and protein content in foliar tissues than WT seedlings, in addition to lower concentrations of lipids and carbohydrates stored in cotyledons. The chloroplasts of albino seedlings were poorly developed, with an undefined internal membrane system and the presence of plastoglobules. Wild‐type seedlings had a uniseriate and hypoestomatic epidermis. The mesophyll was dorsiventral, consisting of a layer of palisade parenchyma and two to four layers of spongy parenchyma. In albino seedlings, the spongy parenchyma was compact, with few intercellular spaces, and the thickness of the mesophyll was larger, resulting in increased thickness of the leaf blade. Albino seedlings had higher stomatal density and number of pavement cells, although the stomata had smaller dimensions. In addition to the partial loss of chlorophylls, albino D. regia showed changes at physiological and structural levels, demonstrating the crucial nature of photosynthetic pigments during the development and differentiation of plant leaf tissues/cells. Abstract : Beyond the loss of chlorophyll, changes in the synthesis of photosynthetic pigments cause stereotyped functional and structural disorders that are also related to albinism in plants.